Effect of cantilever length and alloy framework on the stress distribution in peri-implant area of cantilevered implant-supported fixed partial dentures - Valdey SUEDAM; Rafael Tobias MORETTI NETO; Edson Antonio Capello SOUSA; José Henrique RUBO (University of São Paulo, 2016)
ABSTRACT Because many mechanical variables are present in the oral cavity, the proper load transfer between the prosthesis and the bone is important for treatment planning and for the longevity of the implant-supported fixed partial denture. Objectives To verify the stress generated on the peri-implant area of cantilevered implant-supported fixed partial dentures and the potential effects of such variable. Material and Methods A U-shaped polyurethane model simulating the mandibular bone containing two implants (Ø 3.75 mm) was used. Six groups were formed according to the alloy's framework (CoCr or PdAg) and the point of load application (5 mm, 10 mm and 15 mm of cantilever arm). A 300 N load was applied in pre-determined reference points. The tension generated on the mesial, lingual, distal and buccal sides of the peri-implant regions was assessed using strain gauges. Results Two-way ANOVA and Tukey statistical tests were applied showing significant differences (p<0.05) between the groups. Pearson correlation test (p<0.05) was applied showing positive correlations between the increase of the cantilever arm and the deformation of the peri-implant area. Conclusions This report demonstrated the CoCr alloy shows larger compression values compared to the PdAg alloy for the same distances of cantilever. The point of load application influences the deformation on the peri-implant area, increasing in accordance with the increase of the lever arm.